Synthesis of Chitosan–Ignosulfonate Composite as an Adsorbent for Dyes and Metal Ions Removal from Wastewater - Gu, Fei; Geng, Jing; Li, Meiling; Chang, Jianmin; Cui, Yong (ACS omega, 2019)
Sodium lignosulfonate is a polymer with extensive sources and abundant functional groups. Therefore, it has potential value for research and wide utilization. In this study, the adsorption material was prepared by blending sodium lignosulfonate and chitosan, which could adsorb anionic and cationic dyes and metal ions. The composite was characterized by Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), and thermogravimetry (TG). The results showed that the composite was cross-linked mainly by the strong electrostatic interaction between the protonated amino group in chitosan and the sulfonate group in sodium lignosulfonate. Moreover, the effects of initial concentration, adsorption time, initial pH, and mass ratio of chitosan to sodium lignosulfonate on the adsorption performance of the composite were investigated. Meanwhile, the adsorption processes were agreed well with the pseudo-second-order kinetic model and Langmuir isotherm model. The adsorption mechanism was that the electrostatic interaction between the protonated amino and hydroxyl groups of the composite with anionic (SO3 –) and HCrO4 – groups of Congo red and Cr(VI), respectively. In addition, the electrostatic interaction between SO3 – of the composite and positively charged group of Rhodamine B played an important role in the adsorption of Rhodamine B.